BOARD COMPOSITION AND FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Motunrayo E Omolehin; Folashade O Obaje; Abdulmumuni Ogirima (Malete Journal of Accounting and Finance)
The performance of banks has been identified as critical to the development of any economy. The boards of these banks also occupy a critical role in their performance as they are responsible for the long term success of the banks. It has become a big question what board composition is appropriate for effective performance of corporate organizations of which banks are not exceptional. This study therefore examined the effect of board composition on the financial performance of listed deposit money banks in Nigeria. Five (5) banks were randomly sampled and studied over a six year period (2012-2017). Data collected from various annual reports and accounts were analyzed using Ordinary Least Square Regression analysis. Results show that board size has negative significant effect on the financial performance of listed deposit money banks in Nigeria while non-executive directors have positive significant effect on the financial performance of listed deposit money banks in Nigeria. This study recommends among others, a board size composition of ten and a maximum of fifteen (15) for deposit money banks depending on the scale and complexity of the bank without prejudice for skills, competence, independence and availability of meetings. This study also recommends in line with corporate governance codes that emphasis be placed on non-executive directors although with great care and considerations given to skills, competence, experience, independence and availability for meetings.